"Structures of fantasy and fantasies of structures": Engaging the Aesthetic Self - Clarkson, Austin (Current Musicology, 2005)
The past and present interflow as the years scroll by since the first issue of Current Musicology came off the press. The welcome invitation from the present editor to contribute an essay to celebrate the fortieth anniversary en-courages me to knit together those beginnings with current doings. Recently I offered some fugitive thoughts on the founding of CM (Clarkson 2000), but here, borrowing a leaf from Walt Whitman, I shall look for the larger patterns that emerge from the warp of these days and the weft of those. To begin with, please forgive a brief memoir of my days in Dodge Hall before I explore "experience afterwards, bringing strange developments."